A novel Chilean salmon fish backbone-based nanoHydroxyApatite functional biomaterial for potential use in bone tissue engineering - Muñoz, F.; Haidar, Z. S.; Puigdollers, A.; Guerra, I.; Padilla, M. Cristina; Ortega, N.; García, M. J. (Frontiers in Medicine, 2024)
Given the ensuing increase in bone and periodontal diseases and defects, de novo bone repair and/or regeneration strategies are constantly undergoing-development alongside advances in orthopedic, orodental and cranio-maxillo-facial technologies and improvements in bio-/nano-materials. Indeed, there is a remarkably growing need for new oro-dental functional biomaterials that can help recreate soft and hard tissues and restore function and aesthetics of teeth/dentition and surrounding tissues. In bone tissue engineering, HydroxyApatite minerals (HAp), the most stable CaP/Calcium Phosphate bioceramic and a widely-used material as a bone graft substitute, have been extensively studied for regenerative medicine and dentistry applications, including clinical use. Yet, limitations and challenges owing principally to its bio-mechanical strength, exist and therefore, research and innovation efforts continue to pursue enhancing its bio-effects, particularly at the nano-scale. Herein, we report on the physico-chemical properties of a novel nanoHydroxyApatite material obtained from the backbone of Salmon fish (patent-pending); an abundant and promising yet under-explored alternative HAp source. Briefly, our nanoS-HAp obtained via a modified and innovative alkaline hydrolysis-calcination process was characterized by X-ray diffraction, electron microscopy, spectroscopy, and a cell viability assay. When compared to control HAp (synthetic, human, bovine or porcine), our nanoS-HAp demonstrated attractive characteristics, a promising biomaterial candidate for use in tissue engineering.